Membangun Transparansi dan Efisiensi Keuangan Sekolah Melalui Rencana Anggaran Kegiatan Sekolah dan Sistem Aset Terintegrasi - Maryanti, Eny; Sari, Herlinda Maya Kumala; Dewi, Ade Annisa (Universitas Muhammadiyah Mataram, 2025)
Abstract: The main problem faced by School X Surabaya is the lack of transparency and accountability in financial management and inaccuracies in recording school assets. This condition is caused by the absence of actual expenditure reports in the School Activity and Budget Plan (RKAS) and an asset management system that has not been standardized. The purpose of this Abdimas Program is to increase transparency, accountability, and efficiency of financial management and improve the asset recording system through the development of an integrated RKAS system and the implementation of an asset management system based on asset condition classification. The implementation method includes identification of funding sources, budget preparation and monitoring, asset inventory, training for financial staff, and periodic evaluation. The results showed significant improvements in the accuracy of financial reports, the efficient use of funds and the reliability of asset data. The active participation of the school community and parents also strengthened the sustainability of the program. With a more structured system, Sekolah X Surabaya is expected to become a model of good practice in financial and asset governance in primary education.Abstrak: Permasalahan utama yang dihadapi Sekolah X Surabaya adalah rendahnya transparansi dan akuntabilitas dalam pengelolaan keuangan serta ketidakakuratan dalam pencatatan aset sekolah. Kondisi ini disebabkan oleh belum adanya laporan pengeluaran aktual dalam Rencana Kegiatan dan Anggaran Sekolah (RKAS) serta sistem manajemen aset yang belum terstandar. Tujuan dari Program Abdimas ini adalah untuk meningkatkan transparansi, akuntabilitas, dan efisiensi pengelolaan keuangan serta memperbaiki sistem pencatatan aset melalui pengembangan sistem RKAS terintegrasi dan penerapan sistem manajemen aset berbasis klasifikasi kondisi aset. Metode pelaksanaan meliputi identifikasi sumber pendanaan, penyusunan dan pemantauan anggaran, inventarisasi aset, pelatihan bagi staf keuangan, serta evaluasi berkala. Hasil kegiatan menunjukkan adanya peningkatan signifikan dalam keakuratan laporan keuangan, efisiensi penggunaan dana, dan keandalan data aset. Partisipasi aktif komunitas sekolah dan orang tua turut memperkuat keberlanjutan program. Dengan sistem yang lebih terstruktur, Sekolah X Surabaya diharapkan menjadi model praktik baik dalam tata kelola keuangan dan aset di lingkungan pendidikan dasar.